¿En qué anda la enseñanza de gramática en la actualidad? Una mirada plurilingüe desde el Sur - Arias, Juan José; Mare, Maria; Cvejanov, Sandra; López Grisolía, Virginia; Malalel, Deborah; Ramundo, Guadalupe; Zidarich, Mónica (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2023)
In this interview specialists in different languages (Argentine Sign Language, Wichi, Spanish and English) answer five questions on the teaching of grammar and reflect upon the challenges and problems in the field. The interview includes translations into Argentine Sign Language. Key words: Wichi – Spanish – English – Argentina Sign Language – Grammar